Diabetes-Related Quality of Life: Learning From Individuals Making Lifestyle Changes to Improve Type 2 Diabetes Control. Issue 2 (April 2023) - Fishman, Sarah R.; Fernandez Galvis, Maria A.; Linnell, Jill; Iribarren, Pia; Jonas, Victoria H.; Gittleman, Jennifer M.; Tanenbaum, Molly; Scherer, Maya; Weiss, Linda; Walker, Elizabeth A.; Crespo-Ramos, Gladys; Hoogendoorn, Claire J.; et al.
Purpose: The purpose of this study was to explore how treatment adherence and lifestyle changes required for glycemic control in type 2 diabetes (T2D) are related to quality of life (QoL) among predominantly ethnic minority and socioeconomically disadvantaged adults engaged in making changes to improve T2D self-management. Methods: Adults with T2D in New York City were recruited for the parent study based on recent A1C (≥7.5%) and randomly assigned to 1 of 2 arms, receiving educational materials and additional self-management support calls, respectively. Substudy participants were recruited from both arms after study completion. Participants (N = 50; 62% Spanish speaking) were interviewed by phone using a semistructured guide and were asked to define QoL and share ways that T2D, treatment, self-management, and study participation influenced their QoL. Interviews were analyzed using thematic analysis. Results: QoL was described as a multidimensional health-related construct with detracting and enhancing factors related to T2D. Detracting factors included financial strain, symptom progression and burden, perceived necessity to change cultural and lifestyle traditions, and dietary and medical limitations. Enhancing factors included social support, diabetes education, health behavior change, sociocultural connection. Conclusion: QoL for diverse and socioeconomically disadvantaged adults with T2D is multifaceted and includes aspects of health, independence, social support, culture, and lifestyle, which may not be captured by existing QoL measures. Findings may inform the development of a novel QoL measure for T2D.